Framework for Distributed Database System Using Smart Phone in Cellular Network - Wankhade, Nitin V; Deshpande, S.P (International Journal of Computer Sciences and Engineering, 2025)
Due to advancement in technology and the features the mobile phone users are increasing with tremendous speed so the way of accessing information is changing day by day. Peoples are requiring the information or getting connected to their business when they are on move. The mobile computing applications have given rise to store data on mobile phones. Database developers have created light versions of databases for mobile devices. A trend of storing business-related data on mobile phones has already begun. Large data storage requires different frameworks. A framework for Distributed database system using Smart phone has been presented in this paper.